(untitled) (Research, Society and Development, 2025)
During pregnancy, women can contract sexually transmitted infections, which represent a significant public health problem, directly affecting maternal and fetal health. One of the main infections to be screened during pregnancy is syphilis, as it can be transmitted to the child, resulting in serious consequences, including fetal death, prematurity, and low birth weight. This research aims to conduct a retrospective study using data collected from pregnant patients with syphilis over the last decade in the state of Paraná. The data were obtained through epidemiological and documentary investigation from direct sources, collected from the Department of Informatics of the Unified Health System (DATASUS). Between 2013 and 2023, Paraná recorded 24,535 cases of gestational syphilis, showing a significant increase over the years. Most cases occurred among women aged 20 to 39 years, with low education levels and a predominance of white ethnicity. The data emphasize the urgent need for public policies focused on prevention, early diagnosis, and treatment, with an emphasis on equity and maternal-infant care.